KRITIK TERHADAP TEORI KEKUASAAN-PENGETAHUAN FOUCAULT - Mangihut Siregar (Universitas Wijaya Kusuma Surabaya, 2021)
Power is one of the topics of study in political science. In fact, not a few political science figures state that political science is a science related to power, how to gain power and how to maintain power itself. In political science, power is an ontology that must be achieved, possessed and can be inherited. For Foucault, power is not an ontology but rather a strategy. Power works from the bottom up, not the other way around; power is not concentrated in one person or group of people but its form is spread and is everywhere. Power is practiced in everyday life through discourse. Power is related to knowledge because knowledge does not exist if power does not exist. On the other hand, there can be no power without knowledge. Power and knowledge are an inseparable unity. Science is constructed through discourse. This paper is done through the library method. Through a literature study, it is concluded that Foucault’s thinking is a new view of power. The weakness of Foucault’s view is that he sees everything related to power, power is positive but always experiences resistance. Foucault’s thinking provides a new paradigm in the social sciences in general and political science in particular. Keywords : power, knowledge, discourse